STUDENTS’ INTEREST OF ENGLISH LEARNING BY USING TIKTOK AT GRADE XI OF SMA NEGERI 1 BATANG NATAL - Purba, Happy Sri Rezeki; -, Khairunnisah (Linguistik : Jurnal Bahasa dan Sastra, 2022)
Interest in learning is something that must be improved, if students do not have an interest in learning then lessons given by the teacher will not be absorbed well. Learning English by using Tiktok can help students to increase their interest of English learning. The formulation of the problems in this research are: how are the Students' English Learning interest before using Tiktok at grade XI of SMA Negeri 1 Batang Natal? How are the students’ English learning interest after using Tiktok at grade XI of SMA Negeri 1 Batang Natal? Is there any significant improvement of students’ English learning interest by using Tiktok at grade XI of SMA Negeri 1 Batang Natal? The aim of the research are: to find out the Students' English Learning interest before using Tiktok at grade XI of SMA Negeri 1 Batang Natal, to find out the students’ English learning interest after using Tiktok at grade XI of SMA Negeri 1 Batang Natal, to find out the any significant improvement of students’ English learning interest by using Tiktok at grade XI of SMA Negeri 1 Batang Natal. The researchers used the descriptive qualitative research. In collecting data, researchers used questionnaires and interviews as instrument. The steps used are based on the theory of Miles, Huberman and Saldana, namely data condensation, presentation and drawing conclusion. the 24 students were given a questionnaire and 4 students as interview respondents. The researcher used a closed questionnaire and 4 questions in the interview. The researcher found that students gave positive responses and increased students interest of English learning using Tiktok. Most of the students indicated that they strongly agree with students’ interest of English learning using Tiktok. The researcher found that 75% of students strongly agree that using the Tiktok application can increase students interest of English learning.Keywords: Learning Interest, Tiktok, English